Immobilization of captive tigers (Panthera tigris) with a combination of tiletamine, zolazepam, and detomidine. Issue 1 (18th August 2014) - Laricchiuta, P.; De Monte, V.; Campolo, M.; Grano, F.; Crovace, A.; Staffieri, F.
<x xml:space="preserve">Abstract</x> The aims of this study were to evaluate the effects of the administration of a combination of tiletamine‐zolazepam and detomidine (TZD) in 9 tigers (Panthera tigris). Nine captive tigers were immobilized with tiletamine‐zolazepam and detomidine administered intramuscularly. At the end of the procedure immobilization was partially reversed with atipamezole. Lateral recumbency was achieved in 15.6 ± 5.9 min. The median induction score [scored 1 (excellent) to 4 (poor)] was 1. The immobilization score [scored 1 (poor) to 6 (too deep)] was 5 (4–5) at all study times. After atipamezole administration, all tigers experienced severe ataxia and incoordination. Median recovery score [scored 1 (excellent) to 4 (poor)] was 2.5 (range 2–3). No neurologic and/or important adverse reactions were noticed within 5 days after recovery. The combination tiletamine‐zolazepam with detomidine proved to be effective in immobilizing captive healthy tigers but it maybe associated with hypertension and ataxia during recovery. Zoo Biol. 34:40–45, 2015. © 2014 Wiley Periodicals Inc.